Artificial Intelligence in Sports Education: Current Trends, Applications, and Future Challenges - Choudhury, Jamir Ahmed (Journal of Educational Research and Policies, 2025)
Artificial intelligence (AI) is completely changing the sports education system by transforming conventional approaches and improving training and educational opportunities. This study explores how artificial intelligence (AI) is changing sports education, emphasising its uses, advantages, and drawbacks. We explore how AI technologies like machine learning, computer vision, and data analytics are being used to improve performance analysis, personalize training programs, and streamline decision - making processes by examining current trends and advancements. We demonstrate the practical application of AI in real - world scenarios, such as talent identification, injury prevention, and sports coaching, through in - depth case studies. According to our research, AI - driven solutions that provide individualized learning experiences and data - driven insights greatly increase the efficacy and efficiency of sports teaching. However, there are drawbacks to integrating AI, such as the need for a strong technological foundation and the need to take ethical considerations into account. According to the results of our research, AI has a great deal of promise to improve sports instruction, but a balanced research approach is required to fully realize these benefits and traverse its intricacies. The sports education system can be greatly enhanced by resolving the issues and utilizing AI's potential, opening the door for more knowledgeable and efficient training approaches.